2021
DOI: 10.1088/1755-1315/848/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of tartrazine molecules in water- dimethylsulphaxide solution

Abstract: Spectroscopic and theoretical calculations have shown that the self-aggregation of tartrazine molecules occurs in an aqueous and water-dimethylsulphaxide solution with a hypochromic effect in their electronic spectra. The deformation of the absorption spectra is accompanied by long-wave broadening. The absorption band of the dye E102 self-aggregates corresponds to the maxima λmax=463nm and λmax=483nm. Studies of the linear dichroism spectra have established that tartrazine self-aggregates, which have a needle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…At the same time, it was found that the uneven distribution of charges contributes to the appearance of the dipole moment of molecules. In these cases, the value of the dipole moment in the excited state will be 3 times greater with respect to the values of µ in the ground state ( The results obtained indicate that the botochromicity of the electron spectra, along with the energy of the π electron bonds, also affects the value of the dipole moment of the molecules that contribute to the emergence of the solvation effect [14,15]. Based on these data, it can be concluded that when polar molecules dissolve in hexane as a result of intermolecular interactions (MMV), the potential energy of the solvate increases, which is facilitated by the bathochromic shift of the electron spectra, which is consistent with the experimental results of the molecules [16].…”
mentioning
confidence: 88%
“…At the same time, it was found that the uneven distribution of charges contributes to the appearance of the dipole moment of molecules. In these cases, the value of the dipole moment in the excited state will be 3 times greater with respect to the values of µ in the ground state ( The results obtained indicate that the botochromicity of the electron spectra, along with the energy of the π electron bonds, also affects the value of the dipole moment of the molecules that contribute to the emergence of the solvation effect [14,15]. Based on these data, it can be concluded that when polar molecules dissolve in hexane as a result of intermolecular interactions (MMV), the potential energy of the solvate increases, which is facilitated by the bathochromic shift of the electron spectra, which is consistent with the experimental results of the molecules [16].…”
mentioning
confidence: 88%
“…Прежде всего, нами был исследован спектр поглощения тартразина в воде [26]. При этом установлено, что в спектре длинноволновой полосы поглощения наблюдается максимумом с λмах=426нм.…”
Section: спектроскопия самосборка молекул тартразинаunclassified
“…The following requirements are imposed on the method and device for drying vegetable raw materials in agricultural production [1][2][3][4][5][6][7][8]:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for a long time, the efforts of many scientists [15] were aimed at finding new alternative technologies for drying materials using non-traditional methods of exposure, the main goal of which was and is to reduce the drying time without loss of biologically active substances of the product. In this regard, a number of important theoretical and practical differences between thermal radiation drying of IR radiation from classical methods of heating and heat transfer makes it popular [4,8,15].…”
Section: Introductionmentioning
confidence: 99%